2005
DOI: 10.1002/chem.200401073
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Chiral Complexes of Palladium(0) with 15‐Membered Triolefinic Macrocyclic Ligands

Abstract: The complete structural analysis of the palladium complexes of the triolefinic macrocycles (E,E,E)-1,6,11-tris(arylsulfonyl)-1,6,11-triazacyclopentadeca-3,8,13-trienes, which featured from three identical to three different aryl groups, was achieved by performing X-ray diffraction studies, NMR spectroscopy, and other calculations. The stereochemical complexity is determined by the different isomers formed through complexation of the metal to one or other face of each of the three olefins involved. The palladac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 44 publications
4
23
0
Order By: Relevance
“…The simple 1 H and 13 C NMR spectra of complex 5 confirm the presence of a high symmetry in the molecule. The general conclusions regarding the structure of 5 in solution are in line with those reached after performing detailed NMR studies into similar 15-, 20-and 25-membered azamacrocylic complexes [8]. Each palladium atom coordinates independently with three olefin systems to form a highly rigid five-ring system consisting of consecutively fused three and six-membered rings, as shown in Fig.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The simple 1 H and 13 C NMR spectra of complex 5 confirm the presence of a high symmetry in the molecule. The general conclusions regarding the structure of 5 in solution are in line with those reached after performing detailed NMR studies into similar 15-, 20-and 25-membered azamacrocylic complexes [8]. Each palladium atom coordinates independently with three olefin systems to form a highly rigid five-ring system consisting of consecutively fused three and six-membered rings, as shown in Fig.…”
Section: Resultssupporting
confidence: 70%
“…Mononuclear palladium(0) complexes of types 1-4 ( Fig. 1) have been prepared and fully characterized by means of NMR spectroscopy and X-ray diffraction [8]. These studies have demonstrated that the incorporation of a palladium atom into the cavity of a variety of sizeable polyunsaturated azamacrocyclic ligands forms stable tricoordinate complexes.…”
Section: Introductionmentioning
confidence: 99%
“…These distorsions are observed to a greater extent for the open-chain complex than for the macrocyclic one. For example, the olefinic CC bond distances in 3 (1.376(4) and 1.394(6) Å) are longer than distances in 1 , containing three ferrocenyl units (1.320(3), 1.326(3), and 1.325(3) Å). On the other hand, the loss of planarity, observed by the extent to which the olefinic substituents are bent away from the palladium, is also slightly greater for palladium(0) complex 3 (on average for the three double bonds approximately 19°) than for the macrocyclic complexes 1 (17°) .…”
Section: Resultsmentioning
confidence: 98%
“…One aspect that has attracted our attention throughout the study is the characteristic structural features of complexes 1 , which confer an intrinsic chirality and high stability. The complexation of the metal on one of the two stereotopic faces of each of the olefins present in the structure may form various isomers, of which only the energetically favorable ones are experimentally observed by means of both NMR and X-ray techniques . The conformation of the six-membered chelate rings determines the stability of the compound and, hence, its formation.…”
Section: Introductionmentioning
confidence: 99%
“…A splitting of the signals of the three CH 2 -CHQCH-CH 2 linkages of the macrocycle was observed, both by 1 H and 13 C NMR, as previously described. 29 This is due to the fact that the 3 olefins are not involved in the same manner in the complexation with Pt, and this is complicated by the presence of two different aryl substituents on the macrocycle.…”
Section: Complexation Of Platinum and Obtaining Of Pt Nanoparticle Ne...mentioning
confidence: 99%